Weltharmonik - Kepler, Johannes 1571-1630; Caspar, Max 1880-1956 (Vienna Oldenbourg, 1982)
Kepler began working on Harmonice Mundi sometime near 1599, which was the year Kepler sent a letter to Michael Maestlin detailing the mathematical data and proofs that he intended to use for his upcoming text, which he originally planned to name De harmonia mundi. Kepler was aware that the content of Harmonice Mundi closely resembled that of the subject matter for Ptolemy's Harmonica, but was not concerned. The new astronomy Kepler would use-most notably the adoption of elliptic orbits in the Copernican system-allowed him to explore new theorems. Another important development that allowed Kepler to establish his celestial-harmonic relationships, was the abandonment of the Pythagorean tuning as the basis for musical consonance and the adoption of geometrically supported musical ratios; this would eventually be what allowed Kepler to relate musical consonance and the angular velocities of the planets. Thus, Kepler could reason that his relationships gave evidence for God acting as a grand geometer, rather than a Pythagorean numerologist.
"Über die Harmonik des Ptolemäus und die Harmonielehre des Robert Fludd": p. 357-364.
Übersetzt und eingeleitet von Max Caspar. (Vierter unveränderter Nachdruck der Ausg. von 1939, hrsg. im Auftrag der Bayerischen Akademie der Wissenschaften in München)
Keywords: 17th Century (1601-1700); 20th Century (1901-2000); Science; Geometry; Harmony of the spheres; Harmony; Germany